Effects of Social Enrichment Induced by Different-Sized Groups and Live Bait on Growth, Aggressive Behavior, Physiology, and Neurogenesis in Juvenile Sebastes schlegelii - Zhen Zhang; Xiaoming Yu; Zhongxin Wu; Tao Tian (Fishes)
This study examined the effects of stress and social enrichment on fish neuroplasticity and antioxidant capacity, addressing growing concerns about fish welfare in aquaculture. A 2 × 2 × 2 factorial design comprising eight treatment groups was implemented to investigate how bait type, group size (two distinct sizes tested), and stress level affected the expression of neurogenesis-related genes (PCNA, DCX, and NeuroD) and antioxidant parameters (MDA levels, CAT, GSH-Px, and SOD activity) in the fish. The findings demonstrated that social enrichment significantly reduced aggressive behavior and basal cortisol levels and enhanced the expression of neurogenesis-related gene. However, the optimal group-size augmentation (between the two group sizes tested) considerably increased the activity of antioxidant enzymes and decreased MDA levels. Acute stress further upregulated cortisol levels and the expression of genes related to neurogenesis. A scientific foundation for enhancing fish welfare in aquaculture is provided by the study’s confirmation that social enrichment reduces stress and fosters neuroplasticity.